IMPLEMENTATION MANAGEMENT OF GUIDANCE COUNSELING WITH ISLAMIC VALUES - Arsal, Fathur Riyadhi (Idaarah: Jurnal Manajemen Pendidikan, 2023)
The implementation of counseling guidance obtained by students from educators is expected to increase their trust and devotion to Allah Swt by teaching the principles and guidance contained in the Qur’an and Hadith. Researchers use a type of literature review research. The method used is the thematic tafsir method (maudhu’i). The implementation is to improve the management of counseling guidance implementation by applying Islamic values in the implementation of schedules, availability of infrastructure, and administration of counseling guidance services. The results of the study found that the values that can be applied in the management of counseling guidance implementation are the values of muamalah, akhlakul karimah, and amaliah in the implementation of counseling guidance schedules in the classroom face-to-face once a week. The value of honor in the availability of counseling guidance service infrastructure. The value of mu’awanah and the value of tawhid in finding symptoms of problematic students, causes, and solutions, and the value of trust in the administration of counseling guidance services